DEFINING ACCESSIBILITY OF TOURISM WEBSITES FOR TOURISTS WITH DISABILITIES: A COMPARATIVE STUDY OF UZBEK HOTELS - Kuchkarova, Nigina (Educational Research in Universal Sciences, 2023)
Uzbekistan has become a significant destination for tourists globally, where tourism demand has risen gradually in post-pandemic time. According to the State Statistics Committee, the number of tourists in 2022 increased 2.8 times than it was in the previous year. The growing numbers show the importance of involving tourism suppliers and social entities in developing sufficient accessibility of their websites. Although many studies have examined the accessibility of web sources in the tourism sector worldwide, the research in Uzbekistan is restricted. No studies evaluate the web accessibility of tourism stakeholders for people with disabilities.